ROLE OF HUMAN RESOURCES MANAGEMENT STRATEGY IN ENHANCING ORGANIZATIONAL REPUTATION AN EXPLORATORY STUDY IN BAGHDAD EDUCATION DIRECTORATE, RUSAFA AL-OULA, IRAQ - Isam Fahd Abdul Zahra Budeiri, Asst. Prof. Dr. Sumaya Abbas Majeed (PalArch’s Journal of Archaeology of Egypt / Egyptology, 2021)
The research aims to identify role of human resource management strategy as an independent variable in the organizational reputation adopt edit by Baghdad Education Directorate, Rusafa Al-Awwal. It adopted descriptive approach in conducting the research, and research sample included (general managers, Assistants general managers, Heads of departments, and individual officials). The questionnaire was distributed valid for analysis reached (90) respondents, by adopting a questionnaire form consisting of (40) paragraphs, supported by personal interviews and field livelihoods, provided that you are the researcher. An employee in directorate, and the research approved (SPSS V.25) program, (AMOS V. 18) program, and descriptive statistics methods (arithmetic mean, percentages, standard deviation, linearity test, normal distribution test, factor analysis, relative importance, correlation coefficient. Simple Pearson, simple linear regression, path analysis) to test hypotheses, and the research concluded with the most prominent conclusion that demonstrated hypothesis validity a direct impact on strategy of human resources management, in addition to the weakness of the motivation strategy in the organizations under study. The reciprocity interaction between The strategy of human resources management , the organizational reputation in direct and indirect.